A Bronze Age Round Barrow Cemetery, Pit Alignments, Iron Age Burials, Iron Age Copper Working, and Later Activity at Four Crosses, Llandysilio, Powys. Issue 1 (2nd January 2017) - Havard, Tim; Darvill, Timothy; Alexander, Mary
Abstract : Excavation undertaken at the Upper Severn valley round barrow cemetery at Four Crosses, Llandysilio, Powys, between 2004 and 2006 has increased the known barrows and ring ditches to some twenty-seven monuments within this complex, and revealed additional burials. Based on limited dating evidence, and the data from earlier excavations, the majority of the barrows are thought to be constructed in the Bronze Age. The barrows are considered part of a larger linear cemetery. The landscape setting and wider significance of this linear barrow cemetery are explored within this report. Dating suggests two barrows were later, Iron Age additions. The excavation also investigated Iron Age and undated pit alignments, Middle Iron Age copper working and a small Romano-British inhumation cemetery and field systems. Much of this evidence reflects the continuing importance of the site for ritual and funerary activity.